PELATIHAN LITERASI BATIK BAGI RELAWAN JEPANG DAN PERANCIS DI MUSEUM BATIK PEKALONGAN MELALUI ENGLISH TALK CLUB (ETC) - Ulya, Inayatul; Matra, Sarlita D.; Setianingrum, Ananda; Khakimah (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2026)
Batik Literacy Training represents a strategic effort to promote and safeguard batik as an Indonesian cultural heritage recognized by UNESCO, particularly among international volunteers who act as agents of cultural exchange. Japanese and French volunteers involved in cultural and social programs in Indonesia demonstrated strong interest in local traditions; however, their batik literacy is often constrained by limited understanding of its philosophical meanings, motifs, production processes, and language barriers. This Community Service Program (PkM) aimed to enhance batik literacy and strengthen English communication skills among Japanese volunteers, French volunteers, and members of the English Talk Club (ETC). The program was conducted at the Pekalongan Batik Museum using a participatory and communicative approach grounded in experiential learning. Activities included guided material presentations, direct observation of batik collections, hands-on batik practice, group discussions, and short presentations delivered in English. The participants consisted of international volunteers and ETC members from the Language Centre of Universitas Pekalongan. The results indicated notable improvements in participants’ understanding of batik history, philosophical values, motif diversity, and traditional production techniques, as well as increased speaking confidence, fluency, and acquisition of thematic English vocabulary. Intercultural interactions further fostered reflective dialogue and intercultural communicative competence. In conclusion, integrating cultural literacy with communicative language practice effectively positions the Pekalongan Batik Museum as an intercultural learning space that supports cultural preservation and community-based cultural diplomacy.